Method for improving photoelectric conversion efficiency of perovskite solar cell based on benzene sulfonate material
By using benzenesulfonate materials with multifunctional groups in perovskite solar cells, the problem of high defect state density in perovskite films is solved, and the effect of improving photoelectric conversion efficiency and stability is achieved.
Patent Information
- Application Number
- CN202411898048.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
AI Technical Summary
Existing perovskite solar cells have challenges in improving photoelectric conversion efficiency and stability, mainly because the high density of defect states in perovskite films affects the carrier transmission and recombination process.
A benzenesulfonate material composed of anion and cations, and the cations and anions of this material can interact with MA/FA, I and Pb in perovskites, thereby passivating defects such as vacancies, gaps and inverse positions in perovskite crystals, improving photoelectric conversion efficiency and stability.
By adding benzenesulfonate materials, the photoelectric conversion efficiency of perovskite solar cells is significantly improved, the stability of the device is improved, and the production cost is reduced.
Smart Images

Figure CN119707754A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of perovskite solar cells, and in particular to a method for improving the photoelectric conversion efficiency of perovskite solar cells based on benzenesulfonate materials. Background Art
[0002] Thanks to the extensive use of fossil energy such as oil, natural gas, coal, etc. by humans for hundreds of years, the world economy has developed rapidly. Therefore, modern society is built on the basis of traditional fossil energy. However, the reserves of fossil energy are limited and non-renewable, and the excessive use of fossil energy has an irreversible adverse impact on the ecological environment. Solar energy has the advantages of being inexhaustible, clean and safe. It is the ultimate solution to achieve sustainable development of human society. Continuing to promote the development of the photovoltaic industry will further accelerate the process of energy structure transformation in my country and even the world. Therefore, it is of great significance to develop solar cells with higher photoelectric conversion efficiency and lower production cost.
[0003] In the past decade, organometallic halide perovskite solar cells with low material cost, low processing cost and high photoelectric conversion efficiency have become the most promising candidates for photovoltaic applications. Thanks to the excellent performance and solution processing characteristics of perovskite materials, perovskite solar cells have achieved rapid development in the past decade, and the efficiency has increased rapidly to 26.7%. The device performance of perovskite solar cells is directly related to the crystal quality of the perovskite film, the defects inside the film and at the device interface. Dense, uniform and highly crystalline perovskite films are conducive to the transport of carriers and inhibit the non-radiative recombination of carriers. Therefore, reducing the crystal defects of perovskite films from the source is one of the main ways to improve device performance and stability. Developing new materials for post-processing of devices and directly adding them to perovskite precursors to passivate the interface of the device or passivate the defects of the perovskite body material are important technical means to obtain efficient and stable perovskite solar cells.
[0004] Additives are widely used to improve the crystal quality of perovskite films and reduce the density of internal or interface defects in perovskite films, thereby improving the performance of perovskite solar cells. The main reason is that there are various functional groups in the molecules of additive materials that can interact with the components of perovskite, such as -NH3 + , -Cl, -COOH and -SO3H, etc., thereby passivating the defect state density inside or at the interface of the perovskite film, inhibiting the non-radiative recombination of photogenerated carriers, and improving the photoelectric conversion efficiency of the device. Summary of the invention
[0005] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. The present invention provides a benzenesulfonate material composed of anions and cations and having multiple functional groups to improve the photoelectric conversion efficiency of perovskite solar cells. Both the cations and anions of the material can interact with MA / FA, I and Pb in the perovskite, thereby passivating defects such as vacancies, interstitials and anti-sites in the perovskite crystal, directly improving the photoelectric conversion efficiency and stability of the perovskite solar cell.
[0006] Specifically, the present invention provides the following technical solutions:
[0007] In a first aspect of the present invention, a benzenesulfonate material for a perovskite solar cell is provided, wherein the benzenesulfonate material is represented by the following formula (I):
[0008]
[0009] Wherein, R1 is selected from H, F, Cl, Br, I, C 1-5 Alkyl, NH2, or CF3;
[0010] R2 is selected from NH3 + , (C 1-6 Alkyl)NH3 + NH2 + CH3、CH2NH2 + CH3、CH2NH + (CH3)2, or CH2N + (CH3)3;
[0011] R3 is selected from H, F, Cl, Br, I, C 1-6 Alkyl, NH2, -CF3, OCH3, or NO2.
[0012] The present invention provides a benzenesulfonate material, wherein the cation and anion of the material both contain a benzene ring and have a substituent (R3, R1) at the para position, and the cation and anion can interact with the A, B or X position in the perovskite material to passivate the defects such as vacancies, gaps and anti-positions inside or at the interface of the perovskite, thereby improving the efficiency and stability of the device. The cation part of the benzenesulfonate material mentioned is mainly composed of primary ammonium, secondary ammonium, tertiary ammonium or quaternary ammonium cations, and the anion is a benzenesulfonate radical; the electron-withdrawing or electron-donating properties of R1 and R3 can affect the interaction force between the anion and the cation and the perovskite material, thereby regulating the defect passivation ability.
[0013] Preferably, R1 is selected from Cl, Br, CF3, CH3, CH2CH3, or CH2CH2CH3.
[0014] Preferably, said R2 is selected from NH3+ 、CH2NH3 + 、CH2CH2NH3 + , or CH2CH2CH2NH3 + .
[0015] Preferably, R3 is selected from OCH3, NO2, Cl, Br, or CH3.
[0016] Preferably, R1 is selected from Cl, Br, CH3, or CH2CH3, and R2 is selected from CH2NH3 + 、CH2CH2NH3 + , or CH2CH2CH2NH3 + , wherein R3 is selected from OCH3, Cl, or NO2.
[0017] Preferably, it is selected from the following salts:
[0018]
[0019]
[0020] In a second aspect of the present invention, a perovskite solar cell is provided, comprising a perovskite active layer, wherein the perovskite active layer comprises a perovskite material and the benzenesulfonate material for a perovskite solar cell as described in the first aspect.
[0021] According to an embodiment of the present invention, the molar ratio of the benzenesulfonate material to the perovskite material is (0.01-1): 1. According to a preferred embodiment of the present invention, the molar ratio of the benzenesulfonate material to the perovskite material is (0.03-0.5):1.
[0022] A third aspect of the present invention provides a perovskite solar cell, comprising:
[0023] Conductive substrate;
[0024] A dense layer, the dense layer is disposed on the conductive substrate;
[0025] A mesoporous electron transport layer, wherein the mesoporous electron transport layer is located on the dense layer;
[0026] A mesoporous spacer layer, wherein the mesoporous spacer layer is disposed on the mesoporous electron transport layer;
[0027] A porous counter electrode layer, wherein the porous counter electrode layer is disposed on the mesoporous spacer layer;
[0028] and a perovskite active layer, wherein the perovskite active layer is filled in the pore structures of the porous counter electrode layer, the mesoporous spacer layer and the mesoporous electron transport layer, and the benzenesulfonate material described in the first aspect is added to the perovskite active layer.
[0029] According to an embodiment of the present invention, the conductive substrate is selected from one or more of FTO conductive glass, ITO conductive glass, PET / ITO conductive glass, and PEN / ITO conductive glass;
[0030] The material of the dense layer is selected from one or more of TiO2, SnO2, ZnO, BaSnO3, and SrTiO3;
[0031] The material of the mesoporous electron transport layer is selected from one or more of TiO2, SnO2, ZnO, BaSnO3, and SrTiO3;
[0032] The material of the mesoporous spacer layer is selected from one or more of ZrO2, SiO2, Al2O3, and BaTiO3;
[0033] The material of the porous counter electrode layer is carbon.
[0034] According to an embodiment of the present invention, the benzenesulfonate material is added to the perovskite precursor solution and is jointly filled in the pore structures of the porous counter electrode layer, the mesoporous spacer layer and the mesoporous electron transport layer to obtain the perovskite active layer;
[0035] Alternatively, the method comprises adding a solution containing benzenesulfonate additives to the surface of the porous counter electrode layer for annealing after preparing a perovskite solar cell without benzenesulfonate additives.
[0036] The beneficial effects achieved by the present invention are at least:
[0037] The benzenesulfonate material provided by the present invention is composed of anions and cations, and has the ability to simultaneously passivate multiple types of defects. - 、-NH3 in cation + The benzene ring has defect passivation ability; the properties of the R1 and R3 groups in the anion and cation can be designed to change the steric hindrance and polarity to adjust the defect passivation ability or hydrophilicity of the material; the passivation efficiency is higher, and excellent results can still be achieved on the perovskite solar cell module. The perovskite solar cell prepared by using the provided benzenesulfonate material can improve the photoelectric conversion efficiency. DETAILED DESCRIPTION
[0038] Embodiments of the present invention are described in detail below. The embodiments are exemplary and intended to be used to explain the present invention, but should not be construed as limiting the present invention.
[0039] The present invention provides a benzenesulfonate material for a perovskite solar cell, and the structure of the material is as follows:
[0040]
[0041] R1 is selected from H, F, Cl, Br, I, C 1-5 Alkyl, NH2, or CF3;
[0042] R2 is selected from NH3 + , (C 1-6 Alkyl)NH3 + NH2 + CH3、CH2NH2 + CH3、CH2NH + (CH3)2, or CH2N + (CH3)3;
[0043] R3 is selected from H, F, Cl, Br, I, C 1-6 Alkyl, NH2, -CF3, OCH3, or NO2.
[0044] The defect passivation ability of anions and cations can be regulated based on the electron-withdrawing or electron-donating properties of these substituents and applied to perovskite solar cells to improve the photoelectric conversion efficiency of the cells.
[0045] According to a specific embodiment, R1 is selected from H, F, Cl, Br, I, CH3, CH2CH3, CH2CH2CH3, NH2, CF3. According to a preferred embodiment, R1 is selected from Cl, Br, CF3, CH3, CH2CH3, or CH2CH2CH3.
[0046] According to a specific embodiment, R2 is selected from NH3 + 、CH2NH3+、CH2CH2NH3 + 、CH2CH2CH2NH3 + 、CH(CH3)CH2NH3+、NH2 + CH3、CH2NH2 + CH3、CH2NH + (CH3)2, CH2N + (CH3)3. According to a preferred embodiment, R2 is selected from NH3 + 、CH2NH3 + 、CH2CH2NH3 + , or CH2CH2CH2NH3 + .
[0047] According to a specific embodiment, R3 is selected from H, F, Cl, Br, I, CH3, CH2CH3, CH2CH2CH3, C(CH3)3, NH2, CF3, OCH3, NO2; according to a preferred embodiment, R3 is selected from OCH3, NO2, Cl, Br, or CH3.
[0048] According to a preferred embodiment, R1 is selected from Cl, Br, CH3, or CH2CH3, and R2 is selected from CH2NH3 + 、CH2CH2NH3 + , or CH2CH2CH2NH3 + , wherein R3 is selected from OCH3, Cl, or NO2.
[0049] The cations and anions of the provided materials have dual action sites on the para position of the benzene ring, which can interact significantly with the A, B, and X positions in the perovskite, passivate defects such as vacancies inside the perovskite, and thus improve the efficiency and stability of the device. The cation part is mainly composed of primary ammonium, secondary ammonium, tertiary ammonium or quaternary ammonium cations, and the anion is a benzenesulfonate. It is used for methylamine / formamidine system perovskite solar cells to directly add to the perovskite precursor and post-processing after the device is prepared. According to a specific embodiment, the molar ratio of the benzenesulfonate material to the perovskite material is (0.01-1):1, and the preferred molar ratio is 0.05:1.
[0050] The present invention also provides a perovskite solar cell, comprising:
[0051] Conductive substrate;
[0052] A dense layer, the dense layer is disposed on the conductive substrate;
[0053] A mesoporous electron transport layer, wherein the mesoporous electron transport layer is located on the dense layer;
[0054] A mesoporous spacer layer, wherein the mesoporous spacer layer is disposed on the mesoporous electron transport layer;
[0055] A porous counter electrode layer, wherein the porous counter electrode layer is disposed on the mesoporous spacer layer;
[0056] and a perovskite active layer, wherein the perovskite active layer is filled in the pore structures of the porous counter electrode layer, the mesoporous spacer layer and the mesoporous electron transport layer, and the mentioned benzenesulfonate material is added to the perovskite active layer.
[0057] Among them, the conductive substrate can choose a variety of materials, such as FTO conductive glass, ITO conductive glass, PET / ITO conductive glass, PEN / ITO conductive glass. For example, indium tin oxide (ITO) or fluorine-doped tin oxide (FTO) glass can be used as the substrate of the battery to provide good optical transparency and conductivity. The dense layer is located on the conductive substrate layer, and the commonly used dense layer materials include but are not limited to TiO2, SnO2, ZnO, BaSnO3, SrTiO3, etc. Commonly used mesoporous electron transport layer materials include TiO2, SnO2, ZnO, BaSnO3, SrTiO3, etc. These materials are used to efficiently transfer electrons to the electrode and prevent holes from being transmitted to the cathode. The materials that can be used as mesoporous spacer layers are usually some inorganic oxide materials (such as SiO2, ZrO2, Al2O3). These materials play a role of isolation and protection in perovskite solar cells, and also help to improve the performance of the battery. For example, SiO2 and ZrO2 are often used as spacer layer materials. The spacer layer film prepared by SiO2@ZrO2 nanoparticles has the characteristics of ultra-flatness and crack-free, which can effectively improve the power conversion efficiency of perovskite solar cells. In addition, Al2O3 is also widely used in spacer layer materials, especially when used in combination with ZrO2, which can significantly improve the photoelectric conversion efficiency. According to a specific embodiment, the mesoporous spacer layer material includes but is not limited to ZrO2, SiO2, Al2O3, BaTiO3. The material of the porous counter electrode layer is a carbon material.
[0058] The perovskite active layer is filled in the pore structure of the porous counter electrode layer, the mesoporous spacer layer and the mesoporous electron transport layer. The perovskite active layer includes a perovskite material and the mentioned benzenesulfonate material. The mentioned perovskite material is usually composed of a perovskite material with an ABX3 structure, such as methylamine lead iodine (CH3NH3PbI3), methylamine lead bromide (MAPbBr3), formamidine lead iodine (FAPbI3), formamidine lead bromide (FAPbBr3), cesium lead iodine (CsPbI3), cesium lead bromide (CsPbBr3), methylamine tin iodine (MASnI3), methylamine tin bromide (MASnBr3) and mixed cation, anion perovskite materials and the like. The perovskite material and the benzenesulfonate material can be added dropwise to the mesoporous structure together, left to stand for a period of time, and annealed on a hot stage at 65-70°C for 5-50 hours (according to a preferred embodiment, annealing can be performed at a temperature of 68°C for 10 hours).
[0059] The perovskite solar cell mentioned above can be obtained by a common preparation method in the art. According to a specific embodiment, the benzenesulfonate material is added to the perovskite precursor solution and is jointly filled in the pore structure of the porous counter electrode layer, the mesoporous spacer layer and the mesoporous electron transport layer to obtain the perovskite active layer.
[0060] According to a specific embodiment, after the perovskite solar cell without benzenesulfonate materials is prepared, a solvent containing benzenesulfonate additives may be added to the surface of the porous counter electrode layer for annealing. The annealing mentioned may be achieved at 20-120° C. for 5-60 min.
[0061] Compared with the case where the material mentioned in the present invention is not added, the addition of benzenesulfonate materials can increase the photoelectric conversion efficiency of the perovskite solar cell by up to 8%, or even about 10%. The operation is simple and easy, and the cost is low.
[0062] The technical solution of the present invention is described below by specific examples. It should be noted that these examples are only used to facilitate the understanding of those skilled in the art and should not be regarded as limiting the scope of protection of the present invention. The materials listed in the table of the present invention are used to prepare perovskite solar cells and have been verified to significantly improve the photoelectric conversion efficiency of perovskite solar cells. Without special instructions, the reagents used in the examples can be obtained by commercial purchase or prepared in combination with the common knowledge of those skilled in the art.
[0063] Example 1
[0064] Example 1: A perovskite solar cell was prepared using 4-methoxyphenylethylamine p-chlorobenzenesulfonate as an additive.
[0065] The specific preparation steps are as follows:
[0066] (1) Processing the glass substrate: The glass substrate is processed through three steps: cutting / laser etching and cleaning.
[0067] Cutting: Use a glass cutter to cut the original glass into the required size. Before cutting, make sure the glass surface is clean to avoid defects during the cutting process. After cutting, grind the glass to smooth the sharp edges.
[0068] Laser etching: Use laser etching equipment to adjust the laser power and parameters to control the etching depth and accuracy, and perform high-precision processing on the glass substrate. Laser etching can remove part of the material to form the desired pattern or structure.
[0069] Cleaning: After cutting and laser etching, the glass substrate is cleaned in an ultrasonic cleaner using deionized water and detergent for multiple rounds to remove residual impurities and contaminants. After cleaning, it is spun or dried to ensure that there is no residual moisture on the surface.
[0070] (2) Preparation of dense layer and printing and sintering of three-layer film:
[0071] The di(acetylacetonato)diisopropyl titanate solution is atomized and then sprayed on the FTO surface of the above-mentioned glass, and a dense TiO2 layer is obtained by high-temperature decomposition. After natural cooling, a titanium dioxide electron transport layer, a zirconium dioxide spacer layer, and a carbon counter electrode layer are deposited on the glass sprayed with the dense layer by layer printing. After printing the film layer, P1, P2, P3 and P4 are respectively etched by laser to realize the series connection of the perovskite module, and sintered at the corresponding temperature and retained for use.
[0072] Specifically, a nano-titanium dioxide electron transport layer is deposited on the dense TiO2 layer using screen printing technology to form a mesoporous titanium dioxide film.
[0073] A zirconium dioxide spacer layer is formed on the mesoporous titanium dioxide film by using a screen printing technique, and then dried at 70° C. to remove the solvent, thereby forming a zirconium dioxide film.
[0074] Finally, a carbon counter electrode layer is deposited on the zirconium dioxide film, usually by screen printing or doctor blade technology, and sintered at an appropriate temperature to ensure its stability.
[0075] (3) Preparation of perovskite solution:
[0076] The experiment was divided into a control group and an experimental group, wherein the control group included: 1mmol lead iodide, 1mmol iodomethylamine, and 0.15mmol chloromethylamine were dissolved in 800uL N-methylformamide (NMF), and the obtained perovskite solution was the control group;
[0077] In the experimental group, 4-methoxyphenethylamine chlorobenzenesulfonate was additionally added to the perovskite solution of the control group, and the molar ratio of the added 4-methoxyphenethylamine chlorobenzenesulfonate to the perovskite material was 0.05:1.
[0078] The perovskite solutions of the control group and the experimental group were stirred at 50°C for 2 h and then kept for later use.
[0079] (4) Filling of perovskite solution and crystal growth:
[0080] First, cover the non-filled area with tape, and then use a dispensing machine to drop the prepared perovskite solution on the surface of the carbon film. The filling amount is 300 mg. After standing for a certain period of time, place it on a hot plate at 68°C for annealing for 10 hours. After the solvent is completely removed, the battery preparation process is completed.
[0081] The PCE test of solar cells is carried out by combining a solar simulator and a digital source meter efficiency test system to obtain the JV curve of the test device. Before the test, a standard silicon cell must be used as a reference and the calibrated light intensity must be 1 standard sunlight (AM1.5 G, 100mW / cm 2 ), the effective illumination area is 56.4cm 2PCE (Photovoltaic Conversion Efficiency) refers to the efficiency of solar cells in converting received light energy into electrical energy, and is a key indicator for measuring battery performance. PCE is composed of V OC , J SC and FF jointly determine. OC (Open circuit voltage) refers to the voltage difference between the two ends of a solar cell when the external circuit is disconnected. SC (Short-circuit current density) refers to the current density under short-circuit conditions. FF (fill factor) refers to the maximum power point voltage (V MP ) and open circuit voltage (V OC ) and the maximum power point current (J MP ) product of .
[0082] The following is a comparison of the average performance of batteries in the same batch. OC , J SC , FF, PCE.
[0083] Table 1 Comparison of average battery performance
[0084]
[0085] It can be seen from Table 1 above that the experimental group can improve the Voc of the prepared device and improve the photoelectric conversion efficiency of the battery compared to the control group.
[0086] Example 2
[0087] Example 2 A perovskite solar cell was prepared using 4-nitroamphetamine bromobenzenesulfonate.
[0088] The preparation process is similar to that of Example 1, except that different sulfonate materials are used to prepare the perovskite solution in step (3):
[0089] The control group is: 1mmol lead iodide, 0.15mmol chloromethylamine, 0.25mmol iodomethylamine, 0.75mmol iodomethylamine are weighed and dissolved in 800uL N,N-dimethylformamide (DMF) and 200uL dimethyl sulfoxide (DMSO), and the obtained perovskite solution is the control group;
[0090] The experimental group was prepared by adding 4-nitroamphetamine bromobenzenesulfonate to the above solution (the molar ratio of 4-nitroamphetamine bromobenzenesulfonate to the perovskite material was 0.03:1).
[0091] The performance of the perovskite solar cells in the control group and the experimental group are shown in Table 2:
[0092] Table 2 Battery performance comparison
[0093]
[0094] It can be seen from Table 2 that the experimental group has improved the photoelectric conversion efficiency of the battery compared with the control group.
[0095] Comparison of device performance in Example 3 as post-treatment
[0096] Example 3 prepares a perovskite solar cell by referring to the method of Example 1, except that, in the method of Example 3, no additive is added in advance, and after the solar cell is prepared, a post-treatment process is added, i.e., 2-(4-chlorophenyl)ethylamine methylbenzenesulfonate is added for annealing treatment.
[0097] Specifically include:
[0098] (1) Processing the glass substrate: The glass substrate is processed through three steps: cutting / laser etching and cleaning.
[0099] (2) Preparation of dense layer and printing and sintering of three-layer film:
[0100] The di(acetylacetonato)diisopropyl titanate solution is atomized and then sprayed on the FTO surface of the above-mentioned glass, and a dense TiO2 layer is obtained by high-temperature decomposition. After natural cooling, a titanium dioxide electron transport layer, a zirconium dioxide spacer layer, and a carbon counter electrode layer are deposited on the glass sprayed with the dense layer by layer printing. After printing the film layer, P1, P2, P3 and P4 are respectively etched by laser to realize the series connection of the perovskite module, and sintered at the corresponding temperature and retained for use.
[0101] (3) Preparation of perovskite solution:
[0102] 1mmol lead iodide, 1mmol iodomethylamine, and 0.15mmol chloromethylamine were dissolved in 800uL N-methylformamide (NMF) to obtain a perovskite solution.
[0103] The perovskite solution was stirred at 50 °C for 2 h and then stored for later use.
[0104] (4) Filling of perovskite solution and crystal growth:
[0105] First, cover the non-filled area with tape, and then use a dispensing machine to drop the prepared perovskite solution on the surface of the carbon film. The filling amount is 300 mg. After standing for a certain period of time, place it on a hot plate at 68°C for annealing for 10 hours. After the solvent is completely removed, the battery preparation process is completed.
[0106] (5) Post-processing
[0107] The prepared electronic devices are divided into two groups, among which the experimental group is: 200uL of isopropanol solution of 2-(4-chlorophenyl)ethylamine toluenesulfonate (wherein the concentration of 2-(4-chlorophenyl)ethylamine p-toluenesulfonate in isopropanol is 10mg / ml) is added dropwise on the surface of the porous carbon electrode of the prepared electronic device, and annealed at 60°C for 20min after the addition is completed. The control group devices are treated with the same amount of isopropanol solvent.
[0108] The corresponding battery performance of the control group and the experimental group is as follows:
[0109] Table 3 Device performance comparison results
[0110]
[0111] From the results in Table 3, it can be seen that the photoelectric conversion efficiency of the experimental group is improved compared with the control group.
[0112] In the description of this specification, the description with reference to terms "one embodiment", "some embodiments", "example", "specific implementation" and the like means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention.
[0113] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A benzenesulfonate material for perovskite solar cells, characterized in that: The benzenesulfonate material is shown in the following formula (I): Wherein, R1 is selected from H, F, Cl, Br, I, C 1-5 Alkyl, NH2, or CF3; R2 is selected from NH3 + 、-(C 1-6 Alkyl)NH3 + NH2 + CH3、CH2NH2 + CH3、CH2NH + (CH3)2, or CH2N + (CH3)3; R3 is selected from H, F, Cl, Br, I, C 1-6 Alkyl, NH2, -CF3, OCH3, or NO2.
2. The benzenesulfonate material for perovskite solar cells according to claim 1, characterized in that: The R1 is selected from Cl, Br, CF3, CH3, CH2CH3, or CH2CH2CH3.
3. The benzenesulfonate material for perovskite solar cells according to claim 1, characterized in that: The R2 is selected from NH3 + 、CH2NH3 + 、CH2CH2NH3 + , or CH2CH2CH2NH3 + .
4. The benzenesulfonate material for perovskite solar cells according to claim 1, characterized in that: The R3 is selected from OCH3, NO2, Cl, Br, or CH3.
5. The benzenesulfonate material for perovskite solar cells according to claim 1, characterized in that: Said R1 is selected from Cl, Br, CH3, or CH2CH3, R2 is selected from CH2NH3 + 、CH2CH2NH3 + , or CH2CH2CH2NH3 + , The R3 is selected from OCH3, Cl, or NO2.
6. The benzenesulfonate material for perovskite solar cells according to claim 1, characterized in that: Selected from the following salts:
7. A perovskite solar cell, characterized in that: Comprising a perovskite active layer, wherein the perovskite active layer comprises a perovskite material and the benzenesulfonate material according to any one of claims 1 to 6; Optionally, the molar ratio of the benzenesulfonate material to the perovskite material is (0.01-1):
1.
8. A perovskite solar cell, characterized in that: include: Conductive substrate; A dense layer, the dense layer is disposed on the conductive substrate; A mesoporous electron transport layer, wherein the mesoporous electron transport layer is disposed on the dense layer; A mesoporous spacer layer, wherein the mesoporous spacer layer is disposed on the mesoporous electron transport layer; A porous counter electrode layer, wherein the porous counter electrode layer is disposed on the mesoporous spacer layer; and a perovskite active layer, wherein the perovskite active layer is filled in the pore structures of the porous counter electrode layer, the mesoporous spacer layer and the mesoporous electron transport layer, and the benzenesulfonate material according to any one of claims 1 to 6 is added to the perovskite active layer.
9. The perovskite solar cell according to claim 8, characterized in that: The conductive substrate is selected from one or more of FTO conductive glass, ITO conductive glass, PET / ITO conductive glass, and PEN / ITO conductive glass; The material of the dense layer is selected from one or more of TiO2, SnO2, ZnO, BaSnO3, and SrTiO3; The material of the mesoporous electron transport layer is selected from one or more of TiO2, SnO2, ZnO, BaSnO3, and SrTiO3; The material of the mesoporous spacer layer is selected from one or more of ZrO2, SiO2, Al2O3, and BaTiO3; The material of the porous counter electrode layer is carbon.
10. The perovskite solar cell according to claim 9, characterized in that: The benzenesulfonate material is added to the perovskite precursor solution and is jointly filled into the pore structures of the porous counter electrode layer, the mesoporous spacer layer and the mesoporous electron transport layer to obtain the perovskite active layer; Alternatively, the method comprises adding a solution containing benzenesulfonate additives to the surface of the porous counter electrode layer for annealing after preparing a perovskite solar cell without benzenesulfonate additives.
Citation Information
Patent Citations
Perovskite solar cell capable of inhibiting photolysis of passivation layer and preparation method
CN111640871A
Perovskite composite layer and solar cell
CN115589736A
Perovskite photoelectric device using fluorine-containing sulfonate interface modifier and preparation method thereof
CN116096112A